Skewed Cellular Distribution and Low Activation of Functional T-Cell Responses in SARS-CoV-2 Non-Seroconvertors - Kilpeläinen, Athina; Jimenez-Moyano, Esther; Blanch-Lombarte, Oscar; Ouchi, Dan; Peña, Ruth; Quirant-Sanchez, Bibiana; Perez-Caballero, Raul; Chamorro, Anna; Blanco, Ignacio; Martínez-Caceres, Eva; Paredes, Roger; Mateu, Lourdes; et al. (Frontiers in Immunology, 2022)
The role of T cells in the control of SARS-CoV-2 infection has been underestimated in favor of neutralizing antibodies. However, cellular immunity is essential for long-term viral control and protection from disease severity. To understand T-cell immunity in the absence of antibody generation we focused on a group of SARS-CoV-2 Non-Seroconvertors (NSC) recovered from infection. We performed an immune comparative analysis of SARS-CoV-2 infected individuals stratified by the absence or presence of seroconversion and disease severity. We report high levels of total naïve and low effector CD8+ T cells in NSC. Moreover, reduced levels of T-cell activation monitored by PD-1 and activation-induced markers were observed in the context of functional SARS-CoV-2 T-cell responses. Longitudinal data indicate the stability of the NSC phenotype over three months of follow-up after infection. Together, these data characterized distinctive immunological traits in NSC including skewed cellular distribution, low activation and functional SARS-CoV-2 T-cell responses. This data highlights the value of T-cell immune monitoring in populations with low seroconversion rates response to infection and SARS-CoV-2 vaccination.